[Power Plant at Namasfjord] - Streng, Evelyn Fiedler (1975)
Photograph of a power plant at Namasfjord. A small, yellow and red building sits to the left, white pipes attached to its sides and stretching across the photograph. A grey, dusty, and rocky plain broken up by a mound of rocks to the right sits in the foreground. A dark, pointed mountain is visible in the background, obscured by white steam. An orange, rectangular machine with a vertical pipe to the left of it is visible to the right.